2017
DOI: 10.1557/jmr.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in PCBM/P3HT bilayers, using in situ and ex situ neutron reflectivity

Abstract: In situ and ex situ neutron reflectivity is used to characterize annealed regioregular-P3HT/PCBM bilayers. In situ annealing of a 20 nm PCBM/35 nm P3HT bilayer at 170°C reveals rapid mixing of PCBM and P3HT to produce a polymer-rich layer that contains around 18-20% PCBM. Samples with three different thicknesses of P3HT layer are ex situ annealed at 140°C. This again reveals migration of PCBM into the P3HT and vice versa, with the polymer-rich layer in the 20 nm PCBM/ 35 nm P3HT sample containing 19% PCBM. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…59 Cui et al demonstrated that solubility and solvent choice are key for high performing LbL OPV devices. 59 Numerous studies have since shown the pseudo-bilayer morphology is susceptible to variations in the solvent or cosolvent, 130,[144][145][146]157,167,168,170,173,175,177,187,189 but is also influenced by other parameters such as thermal annealing, 24,132,134,137,152,153,155,156,160,161,181,184,191,193,194 use of additives, 26,166,168,171,176,180,182 or addition of binary components to the donor polymer. 141,143,148,158,161 Cho et al explored how solvent choice influenced morphology and phase separation in P3HT layers.…”
Section: Lbl Opv Device Fabrication By Sequential Spin Coating Processesmentioning
confidence: 99%
“…59 Cui et al demonstrated that solubility and solvent choice are key for high performing LbL OPV devices. 59 Numerous studies have since shown the pseudo-bilayer morphology is susceptible to variations in the solvent or cosolvent, 130,[144][145][146]157,167,168,170,173,175,177,187,189 but is also influenced by other parameters such as thermal annealing, 24,132,134,137,152,153,155,156,160,161,181,184,191,193,194 use of additives, 26,166,168,171,176,180,182 or addition of binary components to the donor polymer. 141,143,148,158,161 Cho et al explored how solvent choice influenced morphology and phase separation in P3HT layers.…”
Section: Lbl Opv Device Fabrication By Sequential Spin Coating Processesmentioning
confidence: 99%
“…The higher flux in conjunction with state-of-the-art detector electronics has led to the possibility of performing single-shot reflectivity measurements in the sub-second range, as demonstrated in x5. This is also increasingly used in user experiments (Zhong et al, 2017;Mô n et al, 2017). The new polarizer and spin flippers have made time-of-flight polarized neutron reflectivity (TOF-PNR) with polarization analysis available, leading to new possibilities in magnetism.…”
Section: Discussionmentioning
confidence: 99%